P-OGC69 Incidence, presentation and long-term sequelae of hiatus hernia after oesophagectomy: a 10-year retrospective cohort study. (16th December 2021) - Chien, Siobhan; Gall, Lewis; Donnelly, Paul; Dreyer, Stephan; Khan, Khurram; MacKay, Colin; Macdonald, Andrew; Craig, Carol; Forshaw, Matthew
Abstract: Background: Hiatus hernia after oesophagectomy is a rare but recognised event, with potentially life-threatening consequences when there is bowel compromise. This 10-year retrospective cohort study aimed to identify the incidence and evaluate the clinical presentation and long-term management of hiatus hernia after oesophagectomy. Methods: We conducted a retrospective analysis of all oesophagectomies performed in a single tertiary centre over a 10-year study period between 2010 and 2019. Demographics, details of the initial procedure and long-term outcomes were analysed. Patients that underwent post-operative computed tomography (CT) imaging at ≥ 12 months post-operatively were included in analysis, with all CT scans independently reviewed by a radiologist. Results: 212 patients were eligible for analysis. 25% (53/212) of patients developed a hiatus hernia post oesophagectomy. Demographic data were similar between patients who developed a hernia compared to those who did not. 75.5% (40/53) of post-operative hiatus hernias developed after transhiatal oesophagectomy (p < 0.001), and patients with post-operative hiatus hernia had a higher BMI (p = 0.009); this association was confirmed on multivariate analysis. Hiatus hernia was frequently under-reported, with only 58.5% (31/53) mentioned on the formal CT report. 81.1% of patients (43/53) were asymptomatic. Operative intervention was only performed in 1 patient presenting with small bowel obstruction as an emergency. Conclusions: Hiatus hernia is a potentially clinically significant and under recognised long-term complication following oesophagectomy, with a significantly higher incidence following transhiatal oesophagectomy and in obese patients. With increasing long-term survival after surgical resection and its preponderance to be found incidentally on cross-sectional imaging, judicious screening for hiatus hernia is warranted to prevent fatal complications.